Effect of temperature and storage duration of Aedes aegypti mosquito specimens artificially infected with dengue-3 virus on the results of immunohistochemical examination - Susilawati Sitti Rohmah Umniyati Tri Baskoro Tunggul Satoto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2012)
To confirm the presence of any dengue viral in a mosquito, mosquito’s head can be squashed ona slide and stained with immunohistochemical staining. The remaining samples then can bestored in the cryo freezer at -80ºC to avoid specimen damage. However, for laboratories withlimited facilities, with only a refrigerator with a temperature range of -20ºC to 4ºC is available,examination to evaluate whether the dengue antigen can still be detected in specimens storedat these temperature is necessary. It was a quasi-experimental study. Three to five-day-old adultfemale Aedes aegypti mosquitoes were injected intrathoracically with dengue-3 (DENV-3) strainH-87 virus and then maintained for about 7 days. The dengue viral antigen on mosquitoes wasidentified using immunohistochemical method after stored at a temperature of 4oC, -20oC, -80oCfor 2, 4 and 8 weeks. Mosquito specimens that were not stored were used as a positive control.Kappa value was counted to analyze level of agreements between two observers. Two-wayAnova was used to analyze mean positive rates. Kappa value showed poor agreement (0.00-0.16) between two observers when the specimens were stored at 4oC for 2-8 weeks, and showedgood agreement (Kappa value of 0.77), when stored at -20oC for 4 weeks. The kappa valueshowed very good agreement (0.90-0.92) when the specimens were stored at -20oC for 2 weeks,and at -80oC for 2-8 weeks. Mean positive rates of the specimens stored at 4oC were significantlylower (p<0.005) than stored at -20oC and -80oC, but there were no significant differencesbetween specimens stored at -20oC and -80oC (p>0.05). In conclusion, availability of thedengue viral antigen on mosquito specimens was influenced by temperature and storage durationof the specimens.Keywords: dengue virus - head squash - immunohistochemistry - kappa agreement - temperature